2x20 Gbps - 40 GHz OFDM Ro-FSO transmission with mode division multiplexing - Amphawan, Angela; Chaudhary, Sushank; Chan, V. W. S. (European Optical Society, 2014)
Radio-over-Free-Space-Optics (Ro-FSO) is a promising technology for future wireless networks.In this work, we have designed a hybrid orthogonal frequency division multiplexing (OFDM) Ro-FSO system for transmission of two independent channels by mode division multiplexing.Two independent 40 GHz radio signals are optically modulated at 20Gbps by mode division multiplexing of two laser modes LG00 and LG10 and transmitted over a free-space link of 20 km to 100 km. The performance of proposed Ro-FSO system is also evaluated under the effect of strong atmospheric turbulences.